Growth Pattern of Early and Late Breast Fed Preterm (30-35 Weeks’ Gestation) Neonates: A Hospital Based Study - Amin, Tahsinul; Chowdhury, MAK Azad; Hossain, M Monir; Hoque, M Mahbubul (Bangladesh Journal of Child Health, 2010)
Background: There is still controversy among the pediatricians regarding when and how to start enteral feeding in preterm neonates. However, early feeding with breast milk was presumed to be well-tolerated, cost-effective and promote growth better than late feeding. Objectives: To compare growth pattern, benefits and risks between early and late breast feeding in preterm (30-35 weeks' gestation) neonates. Methods: This was a randomized controlled trial. Total 100 preterm neonates were stratified into early feeding (n=50) and late feeding (n=50) groups. Early feeding was started on day 3 and late feeding on day 5 of life with expressed breast milk as 20 ml/ kg/day by gavage feeding with daily increment 20 ml/kg till full enteral feeding. Growth was recorded by anthropometric measurements with accuracy and precision for first 3 months of life. Results: Early breast feeding was found to be significantly better than late breast feeding in duration to reach full feeding (13.08 days vs. 16.70 days), time to regain enrolment weight (10.87 days vs. 13.70 days), feed tolerance (78% vs. 58%), hospital stay (13.58 days vs. 16.82 days), mean weight (3773.62 ±310.49 gm vs. 3636.91 ±340.20 gm), linear growth (53.64 ±2.26 cm vs. 52.62 ±2.04 cm) and OFC growth (35.85 ±1.50 cm vs. 35.35 ±1.40 cm) at 3 months of age. Conclusion: Early feeding with breast milk is well tolerated with less morbidity and promotes growth better than late feeding in preterm neonates. Key words: Growth pattern; preterm; breast fed DOI: 10.3329/bjch.v31i1.6071 Bangladesh Journal of Child Health 2007; Vol.31(1-3): 26-31